KAJIAN MORFOLOGIS, FISIOLOGIS DAN GAMBARAN DARAH KUDA (Equus caballus) LOKAL ASLI BIMA - , FRISKA FERARI CHRISTININGRUM; , Dr. drh. Yuriadi M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bima poni is an original horse from Bima district Nusa Tenggara Barat, Indonesia. The population of Bima horse has been decreased and endangered because of that conservation really need to be form. The conservation efforts of this horse can be implemented by knowing the morphology, physiological and the hematology of the horse. The purpose of this study is to determine the morphological data (height, length, width of chest, rim of chest and wide hips), physilogical data (breathing frequency, pulsus frequency and temperature), and blood picture of Bima pony. This study uses five original horses from Bima consists of 3 stallion and 2 mare with ages ranging from 5â12 years old. Each horseshealth checked and measured body temperature, pulsus frequency, breathing frequency, measured body morphology were checked and we took as much as 5 ml the horses blood and then placed it into a tube that had been given EDTA 10%, the blood samples of each horse analyzed in the Laboratory Medicine Faculty of Veterinary Medicine UGM. Based on the result of the reasearch for body morphology of Bima horse can be classified as a pony.Physiological data (pulsus, breathing frequency and temperature) also blood picture there is no difference with other horses.